PENINGKATAN KETERAMPILAN MENYIMAK BERITA MELALUI MEDIA AUDIO VISUAL SISWA KELAS VIII SMP NEGERI 2 SELUMA - Yoza Fitria; Reni Kusmiarti (Universitas Sultan Ageng Tirtayasa, 2026)
This study aims to improve the news listening skills of eighth-grade students of SMP Negeri 2 Seluma through audiovisual media. The method used is quantitative with a One-Group Pretest-Posttest design. The research sample consisted of 20 students who were selected randomly. Data were collected through news listening tests at the pretest and posttest stages, then analyzed by comparing the average scores. The results showed a significant increase from the average pretest score of 58.84 (Quite Capable category) to 82.72 in the posttest (Capable category). This finding proves that audiovisual media is effective in improving listening skills, especially in understanding the elements of 5W + 1H. The implication is that the use of audiovisual media needs to be optimized in Indonesian language learning to improve students' understanding and learning motivation.